PERFORMANCE EVALUATION AND OPTIMIZATION OF KARANJA BIODIESEL FUELLED DIESEL ENGINE (International Journal of Food and Nutritional Sciences, 2022)
Using biodiesel as a diesel fuel substitute is one of the most efficient ways to lower CO2 emissions because it is a green andsustainable energy source. This project's experimental effort focuses on biodiesel made from Pangomia Pinnata oil (Karanjaoil). In comparison to petroleum diesel, the physical and chemical characteristics of Karanja Biodiesel and its mixes arestudied.